Talking Stick Learning Model Assisted by Flashcard Media: Improving Mufradat Learning Outcomes - Luthfi Qolbi Azzahra Wibowo; Iis Dahlia; Yeni Lailatul Wahidah; Agung Setiyawan; Umi Hijriyah; Ahmad Arifin B. Sapar (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to determine the application of the talk stick learning model assisted by flash card media and to determine the level of effectiveness of the talk stick learning model assisted by flash card media in improving mufradat learning outcomes. The study employed a quantitative approach using a one-group pretest-posttest design model. Data were gathered through three methods: (1) watching teacher and student activities during the learning process; (2) using the talking stick model to test what to do before and after; and (3) documenting by gathering research-related documents. The normalcy distribution was used to calculate the One-Sample Shapiro-Wilk Test method, paired sample tests were used to test hypotheses, and N-gain was employed for data analysis. To simplify the process, data analysis was carried out with the help of SPSS 26. This research was conducted at MI Al-Faidizn Buko Poso, Way Serdang class V, totaling 20 students. The research results showed a significance value of 0.000 < 0.05 that Ho was rejected and Ha was accepted, and the N-gain percent value was 85.3492. So the use of the talking stick learning model assisted by flashcard media could improve mufradat learning outcomes.